Chemical Characterisation and Source Attribution of Inorganic Nitrate-based Homemade Explosives - D'Uva, Joshua Adrian (Curtin University, 2022)
This thesis presents a comprehensive investigation into the chemical characterisation, identification, and source attribution of inorganic nitrate-based homemade explosives. The findings demonstrate the potential of linking pre- and post-blast residues to their precursor source using spectroscopic and trace elemental techniques coupled with chemometrics. This provides a significant addition to the forensic intelligence literature and provides a basis for the continuous improvement of forensic chemical analysis and source determination of homemade explosives.